Irish government re-observed - Farrell, B. (Economic & Social Studies, 1975)
In the last paragraph of his most recent work (Chubb 1975) the doyen of Irish political scientists modifies only slightly a judgement originally advanced in 1964. At that time, prompted by Professor Brian Chapman's sharp observation of British government published the previous year, Professor Basil Chubb and David Thornley (1964) cast a cold eye over the operation of democratic processes in Ireland. Irish Government Observed offered one of the earliest critical surveys of the recruitment, role and performance of the Dail deputy, the insufficiencies of Oireachtas procedures and facilities, the inadequacies of the bureaucracy and political parties in presenting real policy choices. It says much both for Chubb's perspicacity and for the inertia of Irish political life that, over a decade later, so, many of the criticisms remain valid.
Keywords: Democracy - Ireland; Politics and government - Ireland